The dynamics of nutrition research in West Africa: Tracking the evidence: Technical note - Transform Nutrition West Africa (International Food Policy Research Institute, 2021)
Transform Nutrition West Africa is a regional initiative to support effective and programmatic action on nutrition through evidence generation, synthesis, and mobilization. This technical provides methodological detail on the evidence tracker that was developed by Transform Nutrition West Africa for the purpose of digesting all nutrition-relevant research evidence published in the West Africa region. Results are presented in the evidence and can be accessed through an online visualization platform.